2017
DOI: 10.7554/elife.21303
|View full text |Cite
|
Sign up to set email alerts
|

The LIM protein complex establishes a retinal circuitry of visual adaptation by regulating Pax6 α-enhancer activity

Abstract: The visual responses of vertebrates are sensitive to the overall composition of retinal interneurons including amacrine cells, which tune the activity of the retinal circuitry. The expression of Paired-homeobox 6 (PAX6) is regulated by multiple cis-DNA elements including the intronic α-enhancer, which is active in GABAergic amacrine cell subsets. Here, we report that the transforming growth factor ß1-induced transcript 1 protein (Tgfb1i1) interacts with the LIM domain transcription factors Lhx3 and Isl1 to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…P14 Tsc1-het and Tsc1-cko adult mouse eyes were dissected and isolated individual retinal cells as described previously 61 . In brief, the cells were incubated in Hank’s balanced salt solution (HBSS) containing 4′,6-diamidino-2-phenylindole (DAPI; 1 μg/ml, final) for 10 min, and fluorescent emitted by DAPI-stained dead cells were detected at 405 nm excitation and 452 nm emission using Beckman Courter Flow Cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…P14 Tsc1-het and Tsc1-cko adult mouse eyes were dissected and isolated individual retinal cells as described previously 61 . In brief, the cells were incubated in Hank’s balanced salt solution (HBSS) containing 4′,6-diamidino-2-phenylindole (DAPI; 1 μg/ml, final) for 10 min, and fluorescent emitted by DAPI-stained dead cells were detected at 405 nm excitation and 452 nm emission using Beckman Courter Flow Cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…Regulation of Pax6 expression in lens and other cell types, including retinal progenitor cells, pancreas cells, and radial glia cells, is an important subject of current investigations [100, 101]. Earlier studies have shown that the mouse Pax6 locus resides within a 420 kb region of chromosome 2 [102] and contains a landscape of interdigitated distal enhancers, many of them being highly conserved throughout vertebrate evolution [103].…”
Section: The “Birth” Of “Visible” Lens Embryologymentioning
confidence: 99%
“…The ChIP assays were performed as described previously with minor modification (Kim et al, 2017). Briefly, 40 mouse eyes were dissected to remove the cornea, lens, and retina.…”
Section: Methods Detailsmentioning
confidence: 99%
“…A CMV-β-gal plasmid (Promega) was co-transfected to normalize transfection efficiencies of individual samples. Cells were harvested 48 hours after transfection and luminescence was evaluated as previously described (Kim et al, 2017).…”
Section: Experimental Model and Subject Detailsmentioning
confidence: 99%